2021
DOI: 10.1101/2021.05.10.21256931
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No safe level of alcohol consumption for brain health: observational cohort study of 25,378 UK Biobank participants

Abstract: Objectives To estimate the relationship between moderate alcohol consumption and brain health, determining the threshold intake for harm and identifying whether population subgroups are at differential risk. Design Observational cohort study. Alcohol consumption was determined at baseline assessment visit using touchscreen questionnaire (2016-10). Multi-modal MRI brain and cognitive testing were performed subsequently (2014-20). Clinical data was extracted from linked Hospital Episode Statistics. Setting … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 67 publications
5
33
0
Order By: Relevance
“…It has been suggested a similar J-or U-shaped relationship exists with brain structure, but only a few MRI studies have found support for this assumption [41][42][43]. More recent large-scale studies of the general population have in fact shown negative linear associations between alcohol consumption and brain structure, showing widespread reductions in grey and white matter volume as well as white matter microstructure and cortical thickness [44][45][46][47]. Taken together, these studies highlight that there is no protective effect of light drinking (e.g., 1-<7 drinks per week) over abstinence and in fact show, similar to alcohol dependence though to a lesser degree, that any level of alcohol consumption can affect brain volume and white matter microstructure.…”
Section: Structural and Volumetric Changes 1structural Alterations In Adultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested a similar J-or U-shaped relationship exists with brain structure, but only a few MRI studies have found support for this assumption [41][42][43]. More recent large-scale studies of the general population have in fact shown negative linear associations between alcohol consumption and brain structure, showing widespread reductions in grey and white matter volume as well as white matter microstructure and cortical thickness [44][45][46][47]. Taken together, these studies highlight that there is no protective effect of light drinking (e.g., 1-<7 drinks per week) over abstinence and in fact show, similar to alcohol dependence though to a lesser degree, that any level of alcohol consumption can affect brain volume and white matter microstructure.…”
Section: Structural and Volumetric Changes 1structural Alterations In Adultsmentioning
confidence: 99%
“…It should be noted that these are cross-sectional association studies, and it is not possible to infer causality or estimate the impact of alcohol on the brain over time. Furthermore, only a small proportion of the variance in brain structure is explained by alcohol consumption [44,46]. A study on brain age further found that only those who drank daily or almost daily showed a difference between chronological and predicted brain age, and there were no differences in those who drank less frequently or abstained from alcohol [48].…”
Section: Structural and Volumetric Changes 1structural Alterations In Adultsmentioning
confidence: 99%
See 3 more Smart Citations